Visualization of Microwave Heatingformesh-Patterned Indium-tin-Oxide by a Thermo-Elastic Optical Indicator Microscope - Zh. Baghdasaryan; Babajanyan, A.; L. Odabashyan; H. Lee; B. Friedman; K. Lee
This review highlights advances toward non-destructive thermo-elastic optical indicator microscopy visualization system, with a particular focus placed on the structural type of the optical indicator. We present the electromagnetic field interaction with a thin electrical conductive layer of mesh-patterned ITO which is used as an optical indicator. Depending on the mesh-pattern orientation and electromagnetic field polarization, the microwave heating mechanism and field distribution are different. Visualization was made with a 12 GHz microwave signal and 35 dBm maximum power.
Keywords: Physics; Materials science; Electronics; radiowave and microwave technology; direct energy conversion and storage